An Analysis of the Role of National Green Tribunal for the Protection & Conservation of Environment - Saini, Mamta (Innovative Research Thoughts, 2017)
The National Green Tribunal (NGT) is a specialised court that was formed in India in 2010 with the purpose of efficiently and promptly resolving matters that are associated with the preservation and protection of the natural environment. The National Green Tribunal (NGT) was established in accordance with the National Green Tribunal Act, which was passed in 2010. The NGT has the authority to hear all civil cases involving issues of environmental law, such as those concerning air and water pollution, waste management, the conservation of forests, and biodiversity. Since it was first established, the NGT has been an essential component in India's efforts to conserve and preserve the country's natural resources. It is one of the NGT's primary strengths that it is able to provide prompt and efficient justice to persons who are seeking the preservation of their constitutional right to live in an unpolluted environment. It has shortened the amount of time required to settle environmental issues, which has resulted in a more streamlined and efficient procedure.